Sistem Pendukung Keputusan Dalam Pemilihan Bidan Terbaik Untuk Wilayah Medan Menerapkan Metode MOORA dengan Pembobotan ROC - Dodi Kurniawan; Pristiwanto Pristiwanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Midwives are professional health workers who have graduated from midwifery education and are registered in accordance with statutory provisions. In practice midwives have attended special training to be able to provide services in the form of midwife care in the form of caring for childbirth and other services. However, the selection of the best midwife, especially at STIKES Indah Medan, is done manually where internal parties make random choices so that complaints are received by patients in their services. In solving this problem, it is better to use a system where selectors can choose the best midwife according to the desired requirements. The system is SPK with Rank Order Centroid weighting through the MOORA (Multi Optimization On The Basis Of Ratio Analysis) method which will produce a solution on the part of STIKES Indah Medan to choose one of the desired midwives